2020
DOI: 10.1007/s40097-019-00328-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and magnetic properties of Ni, Co and FeCo nanoparticles on reduced graphene oxide for removal of Cr(VI)

Abstract: To remove pollutants from industrial waste, magnetic separation by use of magnetic reduced graphene oxide (rGO) is a possible route, due to the high specific surface area of rGO. Reduced graphene oxide decorated with nickel, cobalt and cobalt ferrite nanoparticles was synthesized by means of modified coprecipitation methods. Nitrogen-doped reduced graphene was prepared by a thermal doping method. The resulting composites were characterized with scanning electron microscope, transmission electron microscope (TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In view of the interaction of the surface chemistry of CNTs, some studies have investigated the incorporation of metallic nanoparticles to the surface of CNTs due to their distinctive properties such as antimicrobial activities, catalysis, electricity conduction and high stability for chemicals 27 . Metal nanoparticles such as copper (Cu), iron (Fe), cobalt (Co), nickel (Ni), palladium (Pd), gold (Au), platinum (Pt) and silver (Ag) are frequently used 28 , 29 . Among the metallic nanoparticles (NPs), AgNPs are the most widely utilized in the removal of heavy metals, organic matters, dyes and antibiotics from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the interaction of the surface chemistry of CNTs, some studies have investigated the incorporation of metallic nanoparticles to the surface of CNTs due to their distinctive properties such as antimicrobial activities, catalysis, electricity conduction and high stability for chemicals 27 . Metal nanoparticles such as copper (Cu), iron (Fe), cobalt (Co), nickel (Ni), palladium (Pd), gold (Au), platinum (Pt) and silver (Ag) are frequently used 28 , 29 . Among the metallic nanoparticles (NPs), AgNPs are the most widely utilized in the removal of heavy metals, organic matters, dyes and antibiotics from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Alginate adsorbents have restricted use because of their low mechanical strength and durability. Combining alginates with other materials such as graphene oxide (Mirzaeian et al 2019 ; Malinga and Jarvis 2020 ), activated carbon or graphite with suitable particle size distribution and large pores, high adsorption capacity, and specific surface area (Ahmadi et al 2021 ) has improved their mechanical qualities (Rajabiet al 2017 ). Rajendran et al ( 2021 ) reported that carbon-based materials and their composites are super capacitors due to their high efficiency, superior energy densities, low cost, and prolonged life span (Rajendran et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the efficient doping of 'N' into nanocomposites also helps to improve the sensing ability and that resulted in the lowest detection limit for heavy metal ions. Also, it improves the stability and magnetic properties of graphene nanocomposites [64]. In addition to that, the N doped graphene nanocomposites provide a higher surface area and subsequently provide more site for adsorption of heavy metal ions on the surface of nanocomposites.…”
Section: Sensing Of Cr (Vi)mentioning
confidence: 98%